2006
DOI: 10.1007/s11145-006-9011-4
|View full text |Cite
|
Sign up to set email alerts
|

Derivational morphology and spelling in dyslexia

Abstract: This exploratory study aimed to evaluate the spelling of derived words by dyslexic adolescents and to verify whether this is associated with lack of vocabulary and/ or morphological knowledge. A cross-sectional reading level-design was employed in order to determine differences in spelling, derivational morphology and vocabulary tasks between dyslexic students aged 13+ and age-matched and reading level matched control groups. The study confirmed a profound spelling impairment of dyslexic students in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
63
2
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 28 publications
14
63
2
6
Order By: Relevance
“…The results appear to depend on the kind of control group with which the dyslexics have been compared (chronological-age (CA) control or reading-level (RL) control) and the morphological awareness tasks used. Most studies have shown that children with dyslexia perform less well than their CA controls on morphological awareness tasks involving derivational morphology (Casalis, Colé, & Sopo, 2004;Casalis, Mathiot, Bécavin, & Colé, 2003;Tsesmeli & Seymour, 2006), especially when there is a phonological and/or orthographic change in the derived form (Fowler & Liberman, 1995;Leong, 1989). However, previous studies also report that children with dyslexia perform as well as RL controls in tasks involving the production of word derivations in a sentence context (Fowler & Liberman, 1995) or the production of derived, inflected and compound forms of pseudowords (Elbro, 1989).…”
Section: Phonological and Morphological Knowledge In Dyslexic Studentsmentioning
confidence: 99%
“…The results appear to depend on the kind of control group with which the dyslexics have been compared (chronological-age (CA) control or reading-level (RL) control) and the morphological awareness tasks used. Most studies have shown that children with dyslexia perform less well than their CA controls on morphological awareness tasks involving derivational morphology (Casalis, Colé, & Sopo, 2004;Casalis, Mathiot, Bécavin, & Colé, 2003;Tsesmeli & Seymour, 2006), especially when there is a phonological and/or orthographic change in the derived form (Fowler & Liberman, 1995;Leong, 1989). However, previous studies also report that children with dyslexia perform as well as RL controls in tasks involving the production of word derivations in a sentence context (Fowler & Liberman, 1995) or the production of derived, inflected and compound forms of pseudowords (Elbro, 1989).…”
Section: Phonological and Morphological Knowledge In Dyslexic Studentsmentioning
confidence: 99%
“…It categorizes mistakes in order to offer specific feedback and hints for correcting the misspelled words. In doing so, the children should be encouraged to reflect and think about the language in order to become aware of the word structure [37] and consider these insights in their spelling.…”
Section: The Conceptmentioning
confidence: 99%
“…Children with dyslexia have been shown to perform below chronological-age-(CA-) matched peers on morphological awareness measures in many languages (Berthiaume & Daigle, 2014;Carlisle, 1987;Casalis et al, 2004;Duranovic, Tinjak, & Turbic-Hadzagic, 2014;Egan & Pring, 2004;Egan & Tainturier, 2011;Joanisse, Manis, Keating, & Seidenberg, 2000;Leong, 1999;McBride-Chang et al, 2008;McBride-Chang, Liu, Wong, Wong, & Shu, 2012;Shu, McBride-Chang, Wu, & Liu, 2006;Siegel, 2008;Tsesmeli & Seymour, 2006;Vogel, 1977). They have also been shown to use morphological processes (in reading and spelling) less than age-matched peers Carlisle, Stone, & Katz, 2001;Fisher, Shankweiler, & Liberman, 1985;Hauerwas & Walker, 2003;Leong, 1989).…”
mentioning
confidence: 99%
“…To examine whether children with dyslexia show atypical morphological processing given their level of literacy skills, a better comparison is against younger, reading-ability-matched peers. For the most part, children with dyslexia perform similarly to reading-ability-matched children on oral measures of morphological awareness (Casalis et al, 2004;Egan & Pring, 2004;Egan & Tainturier, 2011;Robertson, Joanisse, Desroches, & Terry, 2012;Tsesmeli & Seymour, 2006). However, the picture for morphological processing is less clear.…”
mentioning
confidence: 99%
See 1 more Smart Citation